2017
DOI: 10.1016/j.jnutbio.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal nutrition and the risk of adult obesity: Long-term effects of nutrition on epigenetic mechanisms regulating gene expression

Abstract: Solid epidemiological evidence indicates that part of the risk of obesity in adulthood could be programmed during prenatal development by the quality of maternal nutrition. Nevertheless, the molecular mechanisms involved are mostly unknown, which hinders our capacity to develop effective intervention policies. Here, we discuss the hypothesis that mechanisms underlying prenatal programming of adult risk are epigenetic and sensitive to environmental cues such as nutrition. While the information encoded in DNA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 262 publications
(226 reference statements)
0
30
0
2
Order By: Relevance
“…The effects on foetal growth, birth defects and the incidence of perinatal death have been particularly striking. There is also growing evidence, not detailed here, that maternal obesity has an impact on the long‐term metabolic and cardiovascular health of their offspring, as well as their mental health, through direct effects of nutrition on epigenetic mechanisms . Prevention strategies are urgently needed and the data shown here indicate that improving physical activity in obese women is beneficial and that bariatric interventions prior to pregnancy must also be considered.…”
Section: Resultsmentioning
confidence: 87%
“…The effects on foetal growth, birth defects and the incidence of perinatal death have been particularly striking. There is also growing evidence, not detailed here, that maternal obesity has an impact on the long‐term metabolic and cardiovascular health of their offspring, as well as their mental health, through direct effects of nutrition on epigenetic mechanisms . Prevention strategies are urgently needed and the data shown here indicate that improving physical activity in obese women is beneficial and that bariatric interventions prior to pregnancy must also be considered.…”
Section: Resultsmentioning
confidence: 87%
“…3 Los cambios ambientales a los que se expone el padre como los contaminantes, la dieta inadecuada, la obesidad, fumar, ingerir bebidas alcohólicas o exponerse a toxinas ocupacionales, tienen impacto en la metilación del DNA, en el incremento de las especies reactivas de oxígeno (ROS), en la modificación de histonas, y en la mayor cantidad de microRNA, 4 lo cual puede conducir a una afectación negativa sobre la concentración, la movilidad y la morfología espermática, conduciendo inclusive a la imposibilidad para fecundar, alteración en el desarrollo embrionario y alteraciones en la descendencia que aumentan el riesgo de desarrollar enfermedades crónicas a futuro. 5,6 La evidencia anterior, hace pensar, que si los estilos de vida poco saludables, se asocian con el detrimento de la salud y de la calidad seminal, estilos de vida saludables en los que se evite el uso del cigarrillo y el licor, se incluya la práctica de actividad física, el descanso y la alimentación adecuadas, podrían tener un impacto positivo en la salud, en el peso y en la composición corporal y por ende, en la calidad seminal.…”
Section: Introductionunclassified
“…An increasing number of studies have suggested that changes in prenatal programming due to an inadequate maternal diet that may result in an adverse intrauterine environment may predispose an individual to long‐term metabolic disorders, even in adulthood . Different nutritional insults in the fetal/maternal environment appear to give rise to similar metabolic disorders in adulthood, suggesting that a common molecular mechanism could be affected during the development of the hypothalamic neural system that regulates energy homeostasis from pregnancy to weaning …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Different nutritional insults in the fetal/ maternal environment appear to give rise to similar metabolic disorders in adulthood, suggesting that a common molecular mechanism could be affected during the development of the hypothalamic neural system that regulates energy homeostasis from pregnancy to weaning. 7,8 Studies have shown that maternal malnutrition alters central leptin and insulin signaling, as well as hypothalamic appetite regulators such as neuropeptide Y (NPY) and proopiomelanocortin (POMC)-expressing neurons. 10,11 Leptin has a neurotrophic role in the development of hypothalamic circuits during a neonatal window of maximum sensitivity, 16 and it is essential in programming neuronal circuits that regulate energy metabolism during adulthood.…”
Section: Introductionmentioning
confidence: 99%